Human papillomavirus-mediated cervical cancer: epigenetic interplay and clinical implications - Sisodiya, Sandeep; Singh, Payal; Joshi, Tannu; Aftab, Mehreen; Firdausi, Nasera; Khan, Asiya; Mishra, Neetu; Jamil Khan, Nida; Tanwar, Pranay; Gupta, Vivek; Hussain, Showket (Frontiers in Microbiology, 2025)
Cervical cancer is a one of the leading causes of mortality in women, and WHO’s initiative to eliminate cervical cancer by 2030 needs to explore several emerging research areas for its elimination such as epigenetics which could play a crucial important role in the cervical cancer pathogenesis driven by persistent high-risk-human papillomavirus infection. Understanding the molecular and epigenetic mechanisms underlying HPV infection and its progression to cancer is critical for advancing prevention, diagnosis, and treatment strategies, which may play a crucial role in eliminating cervical cancer. Persistent infection of human Papillomavirus is intricately linked to the initiation and progression of cervical cancer with different molecular mechanisms, pathways, viral genes, and proteins. HPV-mediated alterations in the host epigenome play a pivotal role in driving oncogenic transformation by modulating gene expression, chromatin dynamics, and DNA methylation patterns, ultimately disrupting normal cellular functions. The relationship between HPV-induced epigenetic changes and cancer progression underscores the virus’s ability to bypass conventional gene-silencing mechanisms. By altering critical regulatory pathways, HPV not only fosters cancerous growth but also influences patient responses to existing treatments, posing challenges to effective disease management. In this current review, we have discussed the role of epigenetic disruptions caused by HPV, which provided a unique opportunity to identify novel therapeutic targets and biomarkers. Epigenetic factors, being reversible and independent of direct genetic manipulation, offer promising avenues for innovative drug delivery strategies. Such approaches could enhance disease management by advancing therapeutic strategies and diagnostics for improving patient outcomes.